Development of nuclear emulsions with 1 μm spatial resolution for the AEgIS experiment - Kimura, Mitsuhiro; Aghion, S.; Ahlén, O.; Amsler, C.; Ariga, A.; Ariga, T.; Belov, A. S.; Bonomi, G.; Bräunig, Philippe; Bremer, J.; Brusa, R. S.; Burghart, G.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2013)
The main goal of the AEgIS experiment at CERN is to test the weak equivalence principle for antimatter. We will measure the Earth's gravitational acceleration g¯ with antihydrogen atoms being launched in a horizontal vacuum tube and traversing a moiré deflectometer. We intend to use a position sensitive device made of nuclear emulsions (combined with a time-of-flight detector such as silicon μ-strips) to measure precisely their annihilation points at the end of the tube. The goal is to determine g¯ with a 1% relative accuracy. In 2012 we tested emulsion films in vacuum and at room temperature with low energy antiprotons from the CERN antiproton decelerator. First results on the expected performance for AEgIS are presented.
Gesehen am 22.06.2022